Toward gentle chokeberry juice production by ultrasound-assisted enzymatic maceration - Nicole Jasmin Nemetz; Anne Ruth Winter; Jan-Peter Hensen; Andreas Schieber; Fabian Weber (Current Research in Food Science, 2023)
Sustainable processes accompanied by high extraction yields and minimized amounts of by-products are a major goal of current fruit juice production. Controlled degradation of cell wall polysaccharides, in particular pectin, may contribute to reduced emergence of side streams. Possible strategies for the optimization are the selection of enzyme preparations based on comprehensive studies of their activities, the adjustment of maceration temperature toward more gentle conditions, and the application of alternative technologies such as ultrasound (US) during maceration. The present study provides insights into the effects of ultrasound-assisted enzymatic maceration (UAEM) on pectin degradation, total anthocyanin content, thermal and storage stability, and juice yield during chokeberry juice production on pilot-plant scale. The two enzyme preparations applied predominantly possessed polygalacturonase or pectin lyase activity. Cell wall polysaccharide degradation was improved by US and resulted in a 3% increase in juice yield by UAEM using an enzyme preparation that shows mostly polygalacturonase activity. Thermostability of anthocyanins was improved in juices produced using pectin lyase and applying US and matched the stability of anthocyanins in juices produced using polygalacturonase. Storage stability of anthocyanins was improved in juice produced using polygalacturonase during UAEM. UAEM also resulted in lower yields of pomace making the production more resource-efficient. Overall, the use of polygalacturonase has promising potential to advance conventional chokeberry juice production by applying US at gentle conditions.